Assessment of complications and success rates of Percutaneous nephrolithotomy: single tract vs. multi tract approaches - Ömür Memik; Onur Karslı (PeerJ)
Purpose The objective of this study was to assess the success and complication rates of single-tract access vs. multi-tract percutaneous nephrolithotomy (PNL). Material and Methods The medical records of consecutive patients who underwent PNL for staghorn, partial staghorn, and complex kidney stones between 2014 and 2022 were retrospectively reviewed. The demographic data, stone volumes, fluoroscopy and operation durations, changes in hemoglobin levels, numbers of blood transfusions, stone-free rates, perioperative complications, duration of nephrostomy removal, and length of hospital stay parameters were noted. The complications and complexity of PNL were graded using the modified Clavien and Guy’s stone scores, respectively. Single and multi-tract subgroups were determined based on PNL access strategy and the subgroups were analyzed. Results The study involved 208 patients, with 158 in the single-tract group and 50 in the multi-tract group. The groups were comparable in age, ASA scores, and comorbidities (p > 0.05). The characteristics of the stones, such as their location, size, and density, did not show any significant differences between the groups (p > 0.05), except for Guy’s stone score, which was higher in the multi-tract group (p = 0.028). The multi-tract group also had significantly longer fluoroscopy and operation times (p < 0.001). There was no statistically significant difference in stone-free rates between the two groups (76.0% vs. 78.0%, p = 0.766). Although the drop in hemoglobin levels was more significant in the multi-tract group (p = 0.027), transfusion rates did not differ significantly between the two groups (p = 0.334). Complication rates were higher in the multi-tract group, but this difference was not statistically significant (p = 0.896). Conclusion This study demonstrated that multi-tract PNL can achieve high stone-free rates with a modest increase in the occurrence of acceptable complications when performed by an experienced surgeon.